Challenges and Prospects of Internal Control in Moroccan Public Administrations in the Era of Artificial Intelligence - Houda HANATY (International Journal of Scientific Research and Innovative Studies, 2025)
This paper examines the challenges and prospects of internal control in Moroccan public administrations within the context of the rapid advancement of Artificial Intelligence (AI). Internal control is a cornerstone of good governance, transparency, and accountability, ensuring efficient use of resources and the reliability of administrative processes. With the rise of AI, internal control systems are undergoing profound transformations, offering both opportunities and risks. On the one hand, AI enhances the automation of repetitive tasks, strengthens fraud detection, and provides predictive analytics for risk management. On the other hand, it raises concerns regarding data privacy, ethical responsibility, algorithmic bias, and over-reliance on technology. This study highlights the regulatory framework governing internal control in Morocco, the practical applications of AI in public administration, and the necessity of adapting existing methods to technological innovations. The findings emphasize that strengthening governance mechanisms, training public agents, and ensuring ethical use of AI are key to maximizing its benefits while minimizing risks. Ultimately, the integration of AI into internal control can significantly improve efficiency, transparency, and trust in public administration, provided that it is implemented within a robust regulatory and ethical framework. Keywords Internal Control; Artificial Intelligence; Moroccan Public Administration; Governance; Transparency; Risk Management; Accountability; Digital Transformation. Received Date: February 25, 2025 Accepted Date: March 18, 2025 Published Date: April 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/450